Eliminating anti-nutritional plant food proteins: the case of seed protease inhibitors in pea. - Alfonso Clemente; Maria C Arques; Marion Dalmais; Christine Le Signor; Catherine Chinoy; Raquel Olias; Tracey Rayner; Peter G Isaac; David M Lawson; Abdelhafid Bendahmane; Claire Domoney (PLoS ONE)
Several classes of seed proteins limit the utilisation of plant proteins in human and farm animal diets, while plant foods have much to offer to the sustainable intensification of food/feed production and to human health. Reduction or removal of these proteins could greatly enhance seed protein quality and various strategies have been used to try to achieve this with limited success. We investigated whether seed protease inhibitor mutations could be exploited to enhance seed quality, availing of induced mutant and natural Pisum germplasm collections to identify mutants, whilst acquiring an understanding of the impact of mutations on activity. A mutant (TILLING) resource developed in Pisum sativum L. (pea) and a large germplasm collection representing Pisum diversity were investigated as sources of mutations that reduce or abolish the activity of the major protease inhibitor (Bowman-Birk) class of seed protein. Of three missense mutations, predicted to affect activity of the mature trypsin / chymotrypsin inhibitor TI1 protein, a C77Y substitution in the mature mutant inhibitor abolished inhibitor activity, consistent with an absolute requirement for the disulphide bond C77-C92 for function in the native inhibitor. Two further classes of mutation (S85F, E109K) resulted in less dramatic changes to isoform or overall inhibitory activity. The alternative strategy to reduce anti-nutrients, by targeted screening of Pisum germplasm, successfully identified a single accession (Pisum elatius) as a double null mutant for the two closely linked genes encoding the TI1 and TI2 seed protease inhibitors. The P. elatius mutant has extremely low seed protease inhibitory activity and introgression of the mutation into cultivated germplasm has been achieved. The study provides new insights into structure-function relationships for protease inhibitors which impact on pea seed quality. The induced and natural germplasm variants identified provide immediate potential for either halving or abolishing the corresponding inhibitory activity, along with associated molecular markers for breeding programmes. The potential for making large changes to plant protein profiles for improved and sustainable food production through diversity is illustrated. The strategy employed here to reduce anti-nutritional proteins in seeds may be extended to allergens and other seed proteins with negative nutritional effects. Additionally, the novel variants described for pea will assist future studies of the biological role and health-related properties of so-called anti-nutrients.